teaching TEACHING NARRATIVE TEXT THROUGH SCAFFOLDING TO NINTH GRADE STUDENT’S OF SMPN 1 KEJURUAN MUDA - Purwati Purwati Purwati (Journal of Education, Linguistics, Literature and Language Teaching, 2018)
The objective of the research was to find whether teaching narrative text through scaffolding is effective to improve the students’ achievement. The population of this researcher was the ninth grade students of SMPN 1 Kejuruan Muda. The subject of the study was 25 students. The sample of this study was the students of SMP Negeri 1 Kejuruan Muda who were in the ninth grade in the academic year of 2011/2012.This Study focuses on narrative text. Before teaching, the researcher gave a test one to the students to know the basic in narrative text. The next meeting the researcher applied practice to teach them. At the last meeting the writer gave a test two in order to know student’s mastery achievement of narrative text. To obtain the relevant data, the researcher used some formulas which supported in analyzing the data. Based on the calculation of the data, it was found that result in test one 67.4 and in the test two was 78.60. It means that students achievement in teaching narrative text through scaffolding because the test two result was better than the test one resultKeywords: Narrative Text, Scaffolding